2012
DOI: 10.1002/cm.21022
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled receptors in neurons: From growth cones to the synapse

Abstract: The Wnt signaling pathway has been implicated in several different aspects of neural development and function, including dendrite morphogenesis, axonal growth and guidance, synaptogenesis and synaptic plasticity. Here, we studied several Frizzled Wnt receptors and determined their differential expression during hippocampal development. In cultured hippocampal neurons, the cellular distributions of Frizzleds vary greatly, some of them being localized at neurites, growth cones or synaptic sites. These findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
(78 reference statements)
1
24
0
Order By: Relevance
“…However, because Wnt-5a regulates synaptic development, we first analyzed the synaptic distribution of FZD9 in cultured hippocampal neurons at day in vitro (DIV) 14. Our immunolocalization studies showed that FZD9 was distributed in a punctate pattern in the neuronal processes, as previously reported (31), and co-localized with the postsynaptic density scaffolding protein PSD-95 (Fig. 1A).…”
Section: Postsynaptic Distribution Of the Fzd9 Receptor In Hippocam-supporting
confidence: 88%
“…However, because Wnt-5a regulates synaptic development, we first analyzed the synaptic distribution of FZD9 in cultured hippocampal neurons at day in vitro (DIV) 14. Our immunolocalization studies showed that FZD9 was distributed in a punctate pattern in the neuronal processes, as previously reported (31), and co-localized with the postsynaptic density scaffolding protein PSD-95 (Fig. 1A).…”
Section: Postsynaptic Distribution Of the Fzd9 Receptor In Hippocam-supporting
confidence: 88%
“…Although the potential roles of Fz receptors in axonal regeneration after CNS injury have not been studied, it should be noted that, under physiological conditions, these receptors are involved in axonal growth and/or function during CNS development [63][67] and adulthood [65], [66]. In agreement with these observations, several Fz receptors are expressed in cultured hippocampal neurons in both their cellular soma and neurites [68]. Interestingly, here we show that in the NL spinal cords, Fz7 is expressed in fine and extremely elongated structures with small engrossments, which may resemble axons.…”
Section: Discussionmentioning
confidence: 54%
“…In addition to central synapses, activity-regulated secretion was also observed at neuromuscular junctions (NMJs) in Drosophila (33). Wnt receptors, especially the Frizzled proteins, are likely located on both the pre- and post-synaptic membrane (11, 34, 35). Thus, the activity-regulated secretion of Wnt proteins may have a biological effect on both the pre- and post-synaptic compartments.…”
Section: Synaptic Activity-regulated Wnt Signalingmentioning
confidence: 99%